Diagnosis, treatment, and management of rickets: a position statement from the Bone and Mineral Metabolism Group of the Italian Society of Pediatric Endocrinology and Diabetology - Baroncelli, Giampiero I.; Comberiati, Pasquale; Aversa, Tommaso; Baronio, Federico; Cassio, Alessandra; Chiarito, Mariangela; Cosci o di Coscio, Mirna; De Sanctis, Luisa; Di Iorgi, Natascia; Faienza, Maria Felicia; Fintini, Danilo; Franceschi, Roberto; et al. (Frontiers in Endocrinology, 2024)
Rickets results from impaired mineralization of growing bone due to alterations in calcium and phosphate homeostasis. Clinical signs of rickets are related to the age of the patient, the duration of the disease, and the underlying disorder. The most common signs of rickets are swelling of the wrists, knees or ankles, bowing of the legs (knock-knees, outward bowing, or both) and inability to walk. However, clinical features alone cannot differentiate between the various forms of rickets. Rickets includes a heterogeneous group of acquired and inherited diseases. Nutritional rickets is due to a deficiency of vitamin D, dietary calcium or phosphate. Mutations in genes responsible for vitamin D metabolism or function, the production or breakdown of fibroblast growth factor 23, renal phosphate regulation, or bone mineralization can lead to the hereditary form of rickets. This position paper reviews the relevant literature and presents the expertise of the Bone and Mineral Metabolism Group of the Italian Society of Pediatric Endocrinology and Diabetology (SIEDP). The aim of this document is to provide practical guidance to specialists and healthcare professionals on the main criteria for diagnosis, treatment, and management of patients with rickets. The various forms of rickets are discussed, and detailed references for the discussion of each form are provided. Algorithms to guide the diagnostic approach and recommendations to manage patients with rare forms of hereditary rickets are proposed.